Modeling of Convergence of the Economic System of Ukraine with G20 Countries Based on the Analysis of Structural Changes in Ukrainian Foreign Trade - SHTAL, Tatyana V.; POLYAKOVA, Yana O.; PROSKURNINA, Nadiia V.; DOBROSKOK, Iulia B.; KOT, Olena V. (Journal of Advanced Research in Law and Economics, 2019)
In the article various theories of convergence of economic systems were considered. Mathematical modeling of the convergence of economic systems was carried out taking into account structural changes in foreign trade. An assessment of the degree of convergence of the economic system of Ukraine was made. The indicators of G20 countries were chosen as the reference economic system for assessing the degree of convergence. On the basis of the calculations of the correlation coefficients and the construction of regression models, it is proved that the valuation assumptions regarding the inclusion of the pieces of information in the model are feasible. A complex mathematical model for assessing the convergence of the developing economic system of Ukraine with the G20 economic systems is proposed. Conclusions about the short-term and long-term prospects for the development of Ukraine’s GDP were made, the measures necessary for the positive development of GDP in each of the prospects were proposed.